An Examination of Chronic Pain Indices and the Updated Posttraumatic Stress Disorder Checklist for Diagnostic and Statistical Manual of Mental-Disorders-Fifth Edition. Issue 11 (10th December 2020) - Lehinger, Elizabeth; Reed, David E; Nabity, Paul; Brackins, Nicole; Villarreal, Robert; McGeary, Cindy; Blount, Tabatha; Cobos, Briana; Jaramillo, Carlos; Eapen, Blessen C; Pugh, Mary Jo; Potter, Jennifer; et al.
ABSTRACT: Introduction: Chronic pain and post-traumatic stress disorder (PTSD) comorbidity is prevalent among veterans and is associated with increased levels of pain severity and pain-related disability. An improved understanding of the relationship between these co-occurring disorders, in addition to effective integrated treatments, will develop by considering the changes to the PTSD diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). The current study examined the relationship between the revised PTSD Checklist for DSM-5 (PCL-5) symptom clusters (i.e., intrusion, avoidance, negative alterations in cognition and mood [NACM], and arousal) and chronic pain measurements (i.e., pain severity, interference, and disability). Materials and Methods: Participants included 103 veterans (ages 26-70, mean = 45.33) participating in a randomized clinical trial examining the efficacy of an interdisciplinary pain management program for chronic musculoskeletal pain. The study was approved by a university system Institutional Review Board and affiliated healthcare system. Results: The participants with a provisional PTSD diagnosis based on PCL-5 responses ( N  = 76) had significantly greater pain severity, interference, and disability than the participants without a provisional diagnosis ( N  = 23). Correlations between symptom clusters and pain measurements were mostly significant and positive with varying strengths. The avoidance symptom cluster, however, had relatively weaker correlations with pain measurements and was not significantly associated with the numeric rating scale of pain severity. Path analyses revealed that, after controlling for avoidance symptoms, significant associations remained between NACM and all the pain measurements. After controlling for NACM symptoms, however, there were no significant associations between avoidance symptoms and pain measurements. Conclusion: The current study highlights a need to re-examine the leading theories about the mutual maintenance of these disorders in order to develop effective integrative treatment approaches. PTSD-related avoidance may have a relatively weaker role in co-occurring chronic pain than the other symptom clusters and may have a qualitatively different role than chronic pain–related avoidance. Future research should explore the relationship between the avoidance in PTSD and the avoidance in chronic pain as well as identify which chronic pain measurements are the most useful when examining the relationship between PTSD and chronic pain. The potential impact of trauma-related cognition and mood on chronic pain indicates that this is an important area for intervention and should be considered in the development of integrated treatments for chronic pain and PTSD among veterans.